Phǣn phatthanā dek læ yaowachon hǣng chāt Phō̜.Sō̜. 2555-2559 : phanūak rūam nayōbāi læ phǣn yutthasāt radap chāt dān kānphatthana dek tām nǣothāng "lōk thī mo̜som samrap dek" Phō̜.Sō̜. 2550-2559 kap yutthasāt čhangwat nāyū samrap dek læ yaowachon (Khana Kammakān Songsœ̄m Kānphatthanā Dek læ Yaowachon hǣng Chāt, 2011)
National children and youths development plan as for 2012-2016, Thailand.